Legal Protection Policy for Obstetricians-Gynecologists in Cases of Maternal, Perinatal, and Neonatal Mortality - Arief Budiono; Ayesha Hendriana Ngestiningrum; Dewi Iriani; Abdullah Al Mamun; Rizka Rizka; Marisa Kurnianingsih (Jurnal Hukum Novelty, 2023)
Introduction to The Problem: Obstetrician-gynecologists (OB-GYNs) must be observant in diagnosing diseases suffered by patients. OB-GYNs who act based on their knowledge can certainly not be blamed if their actions are already according to the procedures. Legal policies protect OB-GYNs in the case of a patient’s death.Purpose/Objective Study: This article aims to analyze the legal protection for OB-GYNs in cases of maternal, perinatal, and neonatal mortalities. Design/Methodology/Approach: This research was a field research with juridical-sociological method conducted in 2021. The researchers conducted interviews with four informants who experienced maternal, perinatal, or neonatal emergencies.Findings: Conditions with a high risk of maternal, perinatal, and neonatal deaths are handled by OB-GYNs. OB-GYNs must be proficient in the standards for obstetric and neonatal emergencies. OB-GYNs who have correctly followed the processes but experienced an accident also have the right to legal protection. In providing health services, OB-GYNs do not only examine the patients, but they also make efforts to recover the patient through treatments. In health law, such efforts of recovery are known as the Therapeutic Agreement. The relationship between obstetricians and patients is bound to a therapeutic transaction. OB-GYNs have the legal obligation to make improvements in their efforts and expertise in healing patients. Legal regulations stipulated in the Indonesian Civil Law are still too general. There  was one case involving dr DASP SpOG and dr HS SpOG, who were sentenced with 10 months in prison because they violated article 39 of the Indonesian Criminal Code because their patient died during the treatment. This case caused unrest among the OB-GYNs. Therefore, there needs to be a law that regulates the relationship between OB-GYNs and their patients. In terms of human rights in Indonesia, this particular healthcare issue is regulated in Law Number 36 of 2009 regarding Health (Indonesian Health Act). Chapter III Article 1 clause (1) and (4) specifially regulate the patients' rights. The legal and ethical responsibilities in health services observe how far the obstetricians' actions have legal implications in cases of errors or negligence in providing health treatments.Paper Type: Research Article